EVALUATION OF FERTILIZER PRODUCED FROM BIO-OIL AND NITROGENOUS COMPOUNDS PROCESS - FANTINATTI, JUSSARA B.; MESA-PEREZ, JUAN M.; ROCHA, JOSÉ D.; CORTEZ, LUÍS A. B.; MORALES, MARINA M.; AGUIAR, ROSA H.; MARTINS, ROBSON C. (Revista Brasileira de Engenharia de Biossistemas, 2009)
Agricultural production in Brazil is increasing due to growing demand for food, in response to thisagricultural residues increase proportionally, requiring a recycle practices to decrease economicsand environmental debits. The purpose of the study was to evaluate slow release fertilizers (F1 andF2) produced from bio-oil. Bio-oil produced from sawdust was submitted to thermochemical reactionswith (NH2)2CO (F1) and bio-oil with NH4OH plus biochar (F2). The hypocotyls growth in maize seedlingwere monitored in mixtures of sandy and fertilizer additions equivalent to 1.2, 2.4, 4.0, 8.0, 16.0, 24.0,32.0 e 40.0 t ha-1, plus a treatment with sandy by itself. Both fertilizers are nitrogen and potassiumsources for plant nutrition. However F2 presented better development for maize seedlings than fertilizerF1.